APPLICATION OF CHITOSAN FROM Peneaus monodon AS COAGULANT OF Pb(II) IN WASTE WATER FROM TOLANGOHULA SUGAR FACTORY KABUPATEN GORONTALO - Astin Lukum; Fajriyanto Djafar (Universitas Gadjah Mada, 2012)
The aim of this research is to remove Pb(II) from waste water of Tolangohula sugar factory, Gorontalo. In this study, coagulation technique was developed using chitosan as coagulant. Chitosan was obtained from Peneaus monodon shell. The effect of coagulant mass was studied by varying the mass of chitosan: 0, 2.5, 5, 7.5 and 10 g. In addition, effect of pH was also examined by varying the pH of solution: 2, 6, 7, 8, 9 and 10. The results showed that the utilization of 10 g chitosan gave the optimal Pb(II) removal of 72.36% or 22.28 x 10-6 mg/g. Additionally, Pb(II) removal was optimum (83%) or 25.44 x 10-6 mg/g at pH 9. It could be concluded that chitosan coagulant had the ability to adsorb the Pb(II) in the waste water from Tolangohula sugar factory Kabupaten Gorontalo.